Transformation of Foundation Law in the Management of Private Higher Education in Indonesia - Alwi, Faisal; Nawi, Syahruddin; Fahmal, Muin; Qamar, Nurul; Mumin, Khadizah Haji Abdul (Indonesian Journal of Legal Community Engagement, 2025)
The Indonesian government has implemented various policies to ensure that higher education management operates in a controlled, structured, and aligned manner with academic norms and national education goals. However, various challenges in the implementation of these regulations, including internal conflicts within foundations, often affect the quality of higher education. This study aims to analyze the impact of internal foundation conflicts on higher education management, education quality, and the achievement of national education goals. Using an empirical legal approach, this research focuses on the role of foundations in managing private higher education institutions in the LLDIKTI Region IX. The analysis is conducted using Good Governance principles involving transparency, accountability, and participation, as well as the theory of Legal Pluralism to understand the relationship between state law and social norms. The findings show that foundations, as nonprofit organizations, face various obstacles due to legal gaps between education providers and implementers. Legal reform is necessary to improve the governance of resources and finances effectively. Legal reforms emphasizing transparency, accountability, and financial sustainability are critical solutions to optimizing the management of private higher education. Governance transformation of foundations is urgently needed for private higher education to sustainably achieve the goals of national education